Pheochromocytoma and tetralogy of Fallot: Coincidence or a rare association?. (January 2016) - Singh, Gagan Deep; Anuradha, Subramanian; Sethi, Prayas; Singla, Sumeet; Saran, Ravindra Kumar; Dewan, Richa
We report the case of a 25-year-old woman with tetralogy of Fallot who presented with chest pain and hypertension, and on further investigation, was diagnosed with a pheochromocytoma in the right adrenal gland. She underwent surgical excision of the tumor. While the simultaneous occurrence of these two diseases is extremely rare, the suspicion of a possible relationship has been raised in the past.